2006
DOI: 10.1021/om060056n
|View full text |Cite
|
Sign up to set email alerts
|

Structures of 1,2-Propadienylgermane (Allenylgermane) and 1,2-Propadienylstannane (Allenylstannane) Determined by Gas-Phase Electron Diffraction and Quantum Chemical Calculations

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The cc-pVTZ-PP(Sn) basis set on the Sn atom has been tested for small organotin molecules, 38,39 where generally good agreement between calculated and experimental structures was obtained. However, there are indications that the bond lengths to the Sn atom are calculated to be too short.…”
Section: Methodsmentioning
confidence: 99%
“…The cc-pVTZ-PP(Sn) basis set on the Sn atom has been tested for small organotin molecules, 38,39 where generally good agreement between calculated and experimental structures was obtained. However, there are indications that the bond lengths to the Sn atom are calculated to be too short.…”
Section: Methodsmentioning
confidence: 99%
“…The differences are obtained from the B3LYP/cc-pVTZ calculations. Uncertainties are estimated total standard deviations (σ tot ) given as σ tot ) [σ 2 scale + (2σ lsq ) 2 ] 1/2 for bond lengths where σ scale ) 0.001r and σ lsq is the least-squares standard deviation using a diagonal weight matrix, and σ tot ) 2σ lsq for the other parameters. σ scale represents uncertainty in the electron wavelength, and 2σ lsq represents additional uncertainties not directly included in the intensity.…”
Section: Gas Electron Diffractionmentioning
confidence: 99%
“…We have previously determined the molecular structure of some small unsaturated organometallic compounds such as vinylstannane, allylstannane, allenylstannane, allenylgermane, and propargylgermane using the gas electron diffraction (GED) method. These investigations are supplemented with quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Recently, the structural and conformational properties of two such compounds, namely, H 2 CdCdCHGeH 3 and H 2 CdCdCHSnH 3 , have been investigated by electron diffraction. 4 A MW study of the corresponding phosphine, H 2 CdCdCHPH 2 , has also been reported. 12 The simple compound allenylsilane, H 2 CdCdCHSiH 3 , has so far not been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…The title compound has not previously been available presumably because the synthesis of this compound, as well as of other propa-1,2-dienyl heterocompounds of group 14 − 16 of the Periodic Table bearing one or more hydrogen atoms on the heteroatom, are difficult. Recently, the structural and conformational properties of two such compounds, namely, H 2 CCCHGeH 3 and H 2 CCCHSnH 3 , have been investigated by electron diffraction . A MW study of the corresponding phosphine, H 2 CCCHPH 2 , has also been reported .…”
Section: Introductionmentioning
confidence: 99%